Approaching the Unknown. The COVID-19 pandemic, political parties and digital adaptations: party élites' perceptions in Italy and Spain - Vittori, Davide; Barberà, Oscar (Frontiers in Political Science, 2023)
During COVID-19 politics was radically transformed. Even though parliaments, parties, and parliamentary groups continued working, they did so mainly through digital means. Our aim is to investigate how political parties and their élites reacted to those changes. For this aim, we launched a pilot survey among party élites in Spain and Italy. We use descriptive statistics and multivariate OLS regressions to answer to our research questions. Our results point out that parties quickly adapted to executive online meetings, but meetings of other (representative) organs were far less frequent. As for the élites' adaptation and in particular privacy concerns, we find that socio-demographic characteristic of the élites matter and being member of a digital party are not crucial determinants, as we expected. Ideology, on the contrary, play a much relevant role, with right-wing élites being more concerned about privacy. Finally, younger and more educated respondents are more favorable toward moving some parties' activities in the on-line sphere.